MANAJEMEN PENGELOLAAN WAKAF PRODUKTIF - Siti Aisyah; Jodi Eriyanto (IZZI: Jurnal Ekonomi Islam, 2021)
The focus of this study aims to analyze the management of productive waqf management. This research method uses qualitative research methods using library research (library research). Data sources that will be the material for this research are books, journals and internet sites related to the selected topic. The data sources for this research consisted of 10 journals. The data analysis technique used in this research is the content analysis method. The results showed that the productive management of waqf is carried out by, among others, collecting, investing, investing, producing, partnerships, trading, agribusiness, mining, industry, educational facilities or health facilities and businesses that are not in conflict with shari'ah.